Otolaryngologic lesions among human immunodeficiency virus-infected children (2018)
Background Otolaryngologic (ORL) lesions are common in children. ORL lesions occur even more commonly and more severely in HIV-infected children. The few avail- able literature has reported a high prevalence in human immunodeficiency virus (HIV)- infected children; however, there are inadequate data on the impact of HIV infection on hearing and the pattern of manifestations of ORL lesions among African children. Objectives This study was conducted to describe the prevalence and manifestations of ORL lesions among HIV-infected children and controls in Nigeria. Materials and Methods A prospective comparative cross-sectional study design was adopted. Clinical evaluation was done, and hearing assessment was done using oto- acoustic emission for all participants and pure tone audiometry for participants aged s 5 years. Hearing thresholds were defined according to the World Health Organization classification. Results One hundred children were studied: 50 HIV-infected and 50 HIV-negative children. The prevalence of ORL lesions among HIV-infected children was 66%, whereas it was 46% (p = 0.044) among HIV-negative children. ORL lesions were more prevalent among children between the 18-month and 5-year age group (p = 0.003) irrespective of HIV status. The lesions that were associated with HIV infection were cervical ade- nopathy (44%, p = 0.010) and hearing loss (36%, p = 0.023). Conclusion The frequency of ORL lesions is high in HIV-infected children, but improved outcomes following use of medications may be responsible for the slight disparity in prevalence when compared with HIV-negative children